Digital Storytelling in Listening EYL Context: Students’ Responses - Febrianti, Esterlita Eka (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
In the contemporary educational landscape, digital storytelling (DST) has surfaced as a promising pedagogical paradigm for facilitating the instruction of English as a Foreign Language (EFL). Nonetheless, its implementation in educational settings has yielded divergent student responses, influencing the efficacy of educational DST as an English language instructional instrument (Baehaki Wahyuni, 2023). This study aims to scrutinize the responses of kindergarten pupils engaged in the DST learning process, with a particular emphasis on nurturing students' listening proficiencies. The investigation was conducted at TK Labschool UPI establishments in Bandung, encompassing a cohort of 10 students aged 5-6 years, employing a qualitative inquiry approach and adopting a case study framework. Data accrual entails classroom observations, while thematic analysis is the methodological scaffold for discerning patterns and discrepancies within the gathered data corpus. The overarching aspiration of this research endeavor is to furnish nuanced insights into the efficacy of DST as a multimodal language acquisition tool in the milieu of kindergarten education. The findings endeavor to elucidate educational practices and enrich the ongoing dialogue of innovative language pedagogical methodologies by augmenting the extant reservoir of knowledge concerning early childhood English language assimilation. The research findings are considered favorable when students exhibit an 80% success rate in behavior and answering questions, indicating a significant response toward achieving the educational objectives.